2023
DOI: 10.55146/ajie.v52i1.335
|View full text |Cite
|
Sign up to set email alerts
|

Te Pā Harakeke: Māori and non-Māori parent (whānau) support of culturally responsive teaching pedagogies

Abstract: This strengths-based paper draws on the qualitative and quantitative survey results from whānau (family members) of tamariki (children) attending 12 schools in an urban area in New Zealand with a high proportion of Māori people. The paper describes the positive impact of effective family engagement on tamariki, from the perspectives of whānau, paying particular interest to the differences between Māori and non-Māori whānau. The views of all whānau who participated in the project support the importance of relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Middle leader participants in this study had less clarity regarding the evidence of the culturally responsive practices likely to positively impact Māori students, with just 24% noting that academic achievement was a useful indicator of success. In a recent study of Māori parents' aspirations for their children, the authors found that most whānau (65%) wanted their children to go onto higher education such as polytech or university [67]. In line with these aspirations, research has long focused on better understanding how school leaders might improve opportunities for Māori students to enter degree-level study after secondary school.…”
Section: Discussionmentioning
confidence: 99%
“…Middle leader participants in this study had less clarity regarding the evidence of the culturally responsive practices likely to positively impact Māori students, with just 24% noting that academic achievement was a useful indicator of success. In a recent study of Māori parents' aspirations for their children, the authors found that most whānau (65%) wanted their children to go onto higher education such as polytech or university [67]. In line with these aspirations, research has long focused on better understanding how school leaders might improve opportunities for Māori students to enter degree-level study after secondary school.…”
Section: Discussionmentioning
confidence: 99%